Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Prestasi Kerja Guru Dengan Semangat Kerja Sebagai Variabel Intervening Di SMA Negeri 1 Sutera - Ringga Pratama Putra; Dori Mittra Candana; Mardhatila Fitri Sopali (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the influence of work discipline and work environment on teacher performance with work morale as an intervening variable at SMA Negeri 1 Sutera. This research uses a quantitative approach with a survey method through Likert-scale questionnaires distributed to 85 respondents. Data analysis was conducted using Structural Equation Modeling based on Partial Least Square (SEM-PLS) with SmartPLS 3.0 software. Model testing was carried out through outer model evaluation including convergent validity, discriminant validity, Average Variance Extracted (AVE), and construct reliability, as well as inner model evaluation using R-square values and direct and indirect effect testing. The results indicate that work discipline has a positive and significant effect on work morale. The work environment has a positive but not significant effect on work morale. Work discipline has a positive and significant effect on teacher performance, while the work environment has a positive but not significant effect on teacher performance. Work morale has a positive and significant effect on teacher performance. Mediation testing shows that work morale mediates the effect of work discipline on teacher performance but does not mediate the effect of the work environment on teacher performance. These findings confirm that improving teacher performance is more strongly driven by work discipline and work morale than by the work environment directly.